Pengaruh Pembelajaran Coding Terhadap Kemampuan Berpikir Logis Pada Anak Usia 5-6 Tahun - LATIFAH, SYIFATUL; Nasikhah, Ikha Durrotun (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Education and stimulation in early childhood are very important. One pivotal aspect of early childhood education that requires special attention is cognitive development. A critical element within this domain that cannot be overlooked is the capacity for logical reasoning. Preliminary observations conducted at RA Zainabiyah Jombang revealed that a number of children aged 5-6 years still face challenges in logical thinking. To address this, coding learning was introduced as an intervention activity to foster these skills. The primary objective of this research was to investigate the impact of coding education on the logical thinking abilities of children aged 5-6 at RA Zainabiyah Jombang. This investigation employed a quantitative methodology utilizing a pre-experimental, one-group pretest-posttest design. A probability sampling method was applied to select the participants. Data was gathered using observation checklists, and the subsequent analysis involved descriptive statistics, prerequisite testing, and t-tests. The findings yielded a significance value of <0.001, which falls well below the 0.05 threshold. Consequently, it can be deduced that coding learning exerts a substantial and meaningful influence on the logical reasoning skills of 5-6-year-old children at RA Zainabiyah Jombang.